Experimental modeling of PEM fuel cells using a new improved seagull optimization algorithm - Yan Cao; Yiqing Li; Geng Zhang; Kittisak Jermsittiparsert; Navid Razmjooy (Energy Reports, 2019)
This study proposes an optimal model to design and simulate the proton exchange membrane fuel cell (PEMFC) systems. The purpose of this paper is to present an improved version of seagull optimization algorithm for optimal parameter identification of the PEMFC stacks. The new algorithm uses the Lévy flight mechanism to give faster convergence rates. The sum of the squared error between the empirical values and achieved optimal model is analyzed based on two empirical PEMFC models including BCS 500-W and NedStack PS6. This analysis is performed to show the potential of the presented method by considering different conditions. Simulation results are compared with several optimization algorithms and show the algorithm's superiority in terms of the solutions quality and the convergence speed.
Keywords: 330; Lévy flight; Modeling; Proton exchange membrane fuel cells; Seagull optimization algorithm